Two novel inhibitory anti-human factor XI antibodies prevent cessation of blood flow in a murine venous thrombosis model - van Montfoort, Maurits L.; Veronique Knaup, L.; Arnoud Marquart, J.; Bakhtiari, Kamran; Castellino, Francis J.; Erik Hack, C.; Meijers, Joost C. M. (Thrombosis and Haemostasis, 2013)
Coagulation factor XI (FXI) is a promising target for anticoagulation, because of its major role in thrombosis and relatively minor role in haemostasis. This implies that inhibition of FXI can prevent thrombosis without causing bleeding. It was our aim to investigate the antithrombotic properties of two novel inhibitory anti-human FXI antibodies (αFXI-175 and αFXI-203). The in vitro properties of both antibodies were analysed using standard clotting assays and calibrated automated thrombography. For the in vivo model we used FXI knockout mice, in which FXI plasma levels were restored with purified human FXI. Thrombosis was induced by applying ferric chloride to the vena cava inferior, after which time to occlusion was analysed. A tail bleeding assay was used to investigate the safety of both antibodies. Using calibrated automated thrombography, both antibodies inhibited thrombin generation initiated via the intrinsic pathway. In contrast, upon tissue factor (TF)-initiated thrombin generation, αFXI-203 did not inhibit thrombin generation, while αFXI-175 inhibited thrombin generation only at low concentrations of TF. In the murine thrombosis model, the vena cava inferior remained patent for 25 minutes (min) in mice treated with αFXI-175 and for 12.5 min in αFXI-203 treated animals, which was significantly longer than in placebo-treated animals (5 min, p<0.05). Neither antibody caused severe blood loss in a tail bleeding assay. In conclusion, the two inhibitory antibodies against FXI prevented cessation of blood flow in a murine thrombosis model without inducing a bleeding tendency.
Keywords: Coagulation; factor XI; thrombosis; murine models